L’habitat intercalaire à la croisée de l’urbanisme tactique et de l’action sociale : les cas de Grenoble, Rennes et Villeurbanne - Adriana Diaconu; Margaux Duran y Gonin (L'Espace Politique)
The rise in homelessness in European cities linked to increased migration has led cities to face new challenges of providing shelter for precarious newcomers. During the COVID-19 pandemic, the French authorities required that all homeless people be sheltered. In order to meet this obligation, they recognised the voluntary actions of activist associations as a resource complementing state action. In this context, the long-standing demand of social movements that vacant buildings be used to house the homeless has gained momentum. This paper addresses the emergence of a non-profit temporary housing model, known as habitat intercalcaire (in-between homes), in France. It originates from the institutionalisation of squatting through regulated occupations of public or private properties that are temporarily unused, to accommodate people who do not qualify for mainstream shelters or social housing. These projects are often included in temporary urbanism strategies of areas undergoing urban renewal. In the academic literature, very few publications examine these practices, especially in France. In other European countries, such as the Netherlands and Switzerland, several authors have analysed temporary housing through the perspective of its commodification (Baloche, 2016; Debrunner, Gerber, 2021). This paper adds to this body of knowledge, through the study of the partnerships between different organisations, activist groups and local authorities in the creation of non-profit temporary housing that integrates rationales both from the social welfare sector and from urban development. By using an actor-centred perspective it complements other studies that have addressed mainstream emergency shelters and “alternative” accommodation for asylum seekers and migrants, such as squats and homestays (Agier et al., 2019; Bouillon, 2009; Damon, 2021; Dietrich-Ragon, 2011; Gardella, 2014, 2016; Lévy, 2021; Roche, 2021). Through an interdisciplinary approach, the paper focuses on the encounter between the discourses, values and practices from the two fields and questions the tactical dimension of these urban actions. It is based on empirical research including participant observation in meetings and seminars organised by the promoters of this non-profit temporary housing model. In addition, interviews with fifteen stakeholders – both from local governments and from the associative sector – were conducted in Rennes, Villeurbanne and Grenoble. The three cities were chosen owing to the involvement of their local political leaders, coming from left-wing or green parties, in reception policies and in housing issues.By focusing on the rationales of the emergence of this housing model, the main findings of the study show how contradictory political and ideological stances have been overcome through pragmatical means, and how the political commitment of elected representatives has fostered different strategies in the three cities. Values originating both from the social welfare and urban development realms, have been combined by advocates of the model, in order to encourage its adoption by property developers. In addition, by facilitating the management of properties by social welfare organisations, these practitioners show they can provide “creative” and financially sustainable long-term solutions for housing the homeless. Finally, the paper shows that these experiments attempt to pacify divergent logics and to include the social issue in urban management on a long-term basis. In doing so, it raises further questions on the future joint evolutions of social welfare and urban planning, when faced with challenges associated with international migration and housing crises.